OPTIMALISASI PENANGANAN SURAT PENGADUAN MASYARAKAT KE DPR RI - Ahmad Budiman (Sekretariat Jenderal DPR RI, 2012)
Maximizing the handling of public complaints to the House, whether received by mail or through media online or “SMS Aspiration” has shown significant results. However, this condition is not comparable with the ability of the of the House to follow up the complaints which is still less than expected. Thus the maximizing the follow up of the public complaints letters is an urgent matter in the parliament, which can be conducted by the complementary bodies of the house to form a special committee or working team to deal with all complaints come from public.